The acceptability and feasibility of a guide for sharing the outcome of a memory assessment - Silvester, Annabelle; De Boos, Danielle; Moghaddam, Nima (2025)
How outcomes of assessments for dementia are communicated is a challenging task to navigate for clinicians, patients, and their companions. Miscommunication can result in negative consequences for health-related outcomes including reduced self-esteem and loss of meaningful roles. Interventions to support communication specific to the diagnosis of dementia are required. A prototype intervention has been developed aiming to promote good practice in Memory Assessment Services. This mixed methods project assessed the acceptability and feasibility of a trial to evaluate effectiveness of the intervention. Framework analysis was used following interviews with five clinicians to produce themes relating to the constructs identified in the Theoretical Framework of Acceptability (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, self-efficacy). Clinicians reported good acceptability of the intervention and willingness to adopt the intervention into their practice. The recruitment strategy was not feasible for patients and companions and therefore acceptability of the intervention was not assessed from their perspective. Explanations for poor recruitment are explored. An alternative study design to investigate the effectiveness of the intervention is required.